Factors Influenced Effectiveness of Health Management for Pre-diabetes People in Khon Kaen Province - Jaklang, Thanut (Journal for Developing the Social and Community, 2017)
Diabetes is the major health problem of the world, which tends to increase steadily. The objectives of this study was to study factors influencing the effectiveness of health management among pre-diabetes in Khon Kaen Province The subjects were 613 pre-diabetics people by using multi-stage sampling. The tool used for the questionnaire was the discriminative power of 0.20-0.78 and the total reliability was 0.98.The statistics used for data analysis were frequency, percentage, mean, standard deviation and pearson’s product moment correlation coefficient, kurtosis, skewness and structural equation model (SEM). The data were analyzed by using the computer software package. Research findings were as: The hypothesis model was consistent with empirical data. The ratio of c2/df was 3.667, RMSEA was 0.066, SRMR was 0.033, CFI was 0.966 and TLI was 0.955. Factors Influencing overall effectiveness of health management for pre-diabetes in Khon Kaen Province were the administrative factors of the district health office had an overall coefficient of influence was 0.791, followed by the health management factor, the potential factor of person and the social support factor, the coefficients of influence were 0.422, 0.390 and 0.389 respectively. All variables can explain the variance of effectiveness of health management for pre-diabetes people in KhonKaen Province was 76.30%.